Evaluating DHI records with the dairy herd analyzer - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1989)
A computer program was developed for analyzing DHI records to evaluate potential losses from 1) reproduction, 2) nutrition, 3) milk quality, and 4) genetics. Production-tested Kansas Holstein herds were grouped according to Rolling Herd Average (RHA), with the groups averaging 13,587, 15,988, 17,938 and 20,227 lb milk/cow/yr. Losses were directly related to RHA, amounting to 573, 426, 300, and 160/cow/yr, respectively. The Dairy Herd Improvement (DHI) program provides valuable information to dairy farmers for making feeding, breeding, and management decisions. Yet, the only economic information provided by the program is feed cost/cwt milk produced and income over feed cost. Hence, the Dairy Herd Analyzer (DHA) computer program was developed to evaluate economic losses in dairy herds, using information from the Herd Summary (DHIA-202) and Somatic Cell Count Report (DHIA-230). The program is intended to be used by dairy farmers, consultants, researchers, and Extension personnel.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; DHI Records; Reproduction; Nutrition; Milk quality; Genetics